2021
DOI: 10.1200/go.21.00096
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Clinical Trials in Africa—An Untapped Opportunity: Recommendations From AORTIC 2019 Conference Special Interest Group in Clinical Trials

Abstract: Cancer is now a formidable health care burden in sub-Saharan Africa (SSA) due to lifestyle westernization and longer life expectancy. The exponential increase in cancer incidence coupled with high mortality rate is not comparable with that seen in westernized countries. To address global cancer disparity, globalization of cancer clinical trials to involve sub-Saharan Africa can serve as a platform where innovative targeted therapies can be made available to patients in the environ. In the 2019 African Organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Yet, global geographical disparities remain in cancer clinical trials for PWH due to the exclusion of sub-Saharan African and Latin American countries—where the burden of HIV and HIV-associated cancers is highest—from cancer clinical trials. 52 Notably, there was a low proportion of black participants in these studies, highlighting previously demonstrated disparities in clinical trial enrollment among racial and ethnic minorities even in high-income countries. 53 54 Expanding ICI clinical trial enrollment for PWH is an important step in reducing barriers to immunotherapy access.…”
Section: Discussionmentioning
confidence: 63%
“…Yet, global geographical disparities remain in cancer clinical trials for PWH due to the exclusion of sub-Saharan African and Latin American countries—where the burden of HIV and HIV-associated cancers is highest—from cancer clinical trials. 52 Notably, there was a low proportion of black participants in these studies, highlighting previously demonstrated disparities in clinical trial enrollment among racial and ethnic minorities even in high-income countries. 53 54 Expanding ICI clinical trial enrollment for PWH is an important step in reducing barriers to immunotherapy access.…”
Section: Discussionmentioning
confidence: 63%
“…Organized neuro-oncology groups and highly specialized brain tumor centers from high performing countries should collaborate with institutions in low-performing regions to build capacity and improve the quantity and quality of experimental neuro-oncology research. 84…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Simpson grading scale with related RFS after surgery to underrepresented and low-resource regions. Organized neuro-oncology groups and highly specialized brain tumor centers from high performing countries should collaborate with institutions in low-performing regions to build capacity and improve the quantity and quality of experimental neuro-oncology research 84. PrognosisMeningiomas generally have a good prognosis, which highly correlates with the histological grade, degree of resection, tumor size, and location.…”
mentioning
confidence: 99%
“…However, there are few trained oncology specialists, low funding for research, and inadequate interprofessional collaboration to sustain patient-centered care. 5 6 there is now a critical mass of experienced personnel conducting clinical trials in communicable diseases such as malaria, tuberculosis, HIV, and neglected tropical diseases. Such expertise could be tapped for ongoing support and in-country experiential training for cancer clinical trial teams, because the understanding of challenges in conducting pragmatic clinical trials in low-and middle-income countries is already there.…”
Section: Addressing Critical Gaps In Interdisciplinary Training and I...mentioning
confidence: 99%